PENGARUH KEUNGGULAN BERSAING TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN SMARTPHONE PADA LORONG CELL CIJENGKOL KAB. SUBANG - Dewi Mulyani; Wida Ningsih; Rendi Bayu Satria (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
The purpose of this study is analysis the influence of competitive advantage on smartphone purchasing decisions at Lorong Cell in Cijengkol, Subang Regency. The subjects of this research were consumers who purchased smartphones at Lorong Cell, with a total sample of 96 respondents. This study employed a quantitative method with a survey approach. The data sources consisted of both primary and secondary data. Data collection was conducted through questionnaires. To measure the extent of the influence of competitive advantage on purchasing decisions, data analysis included validity and reliability tests, normality and linearity tests, correlation analysis, simple linear regression, significance testing (t-test), and the coefficient of determination, assisted by SPSS version 25.0. Based on the results, the competitive advantage of Lorong Cell is categorized as fairly good, as is consumer purchasing decision-making. Hypothesis testing shows that the calculated t-value of 13.740 is greater than the t-table value of 1.985, with a significance level of 0.000 < 0.05. Therefore, it can be concluded that there is a positive and significant influence of competitive advantage on smartphone purchasing decisions at Lorong Cell in Cijengkol, Subang Regency.